1991
DOI: 10.1083/jcb.115.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic behavior of human melanoma cell lines in nude mice correlates with urokinase-type plasminogen activator, its type-1 inhibitor, and urokinase-mediated matrix degradation.

Abstract: Abstract. Five out of six human melanoma cell lines tested were able to degrade in vitro a smooth muscle cell extracellular matrix in a plasmin-dependent way. In three of these five cell lines, this process was mediated by tissue-type plasminogen activator (t-PA) and in the other two cell lines by urokinase-type plasminogen activator (u-PA).All melanoma cell lines produced t-PA mRNA and protein, whereas only the two cell lines showing u-PAmediated matrix degradation produced u-PA mRNA and protein . These latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 54 publications
0
59
1
3
Order By: Relevance
“…Previous studies have shown that BLM and MV3 differ from the other cell lines with respect to factors that influence the metastatic process. They show a strong adherence to extracellular matrix components laminin and collagen types I and IV (Danen et al, 1993, and have a high expression level of the extracellular protease urokinase-type plasminogen activator (uPA) and its inhibitor PAI-I (Quax et al, 1991;Van Muijen et al, 1995). The formation of experimental lung metastasis may be used as an indicator of the metastasizing capacities of a cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BLM and MV3 differ from the other cell lines with respect to factors that influence the metastatic process. They show a strong adherence to extracellular matrix components laminin and collagen types I and IV (Danen et al, 1993, and have a high expression level of the extracellular protease urokinase-type plasminogen activator (uPA) and its inhibitor PAI-I (Quax et al, 1991;Van Muijen et al, 1995). The formation of experimental lung metastasis may be used as an indicator of the metastasizing capacities of a cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Human melanoma cells (BLM cells) [21], were grown in culture flasks in a humidified atmosphere with 5% CO 2 at 37°C. The culture medium was Dulbecco's Modified Eagle Medium with Nutrient Mixture F12 (Gibco, Merelbeke, Belgium), supplemented with 10% (v/v) fetal bovine serum (FBS) (Hyclone, Thermo Scientific, MA, USA), 20 U/ml penicillinstreptomycin (Gibco, Merelbeke, Belgium), 2 mM L-glutamine (Gibco, Merelbeke, Belgium) and 10 mM HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) (Sigma-Aldrich, Diegem, Belgium).…”
Section: Cell Culturementioning
confidence: 99%
“…The plasminogen activators and their inhibitors play a key role in the proteolytic cascade that is responsible for the breakdown of several components of the extracellular matrix, which surrounds the tumour cells. This process results in invasion and subsequently metastasis formation (Dan0 et al, 1985;Saksela, 1985;Vassalli et al, 1991;Ossowski et al, 1991;Quax et al, 1991;Hart, 1992;Schultz et al, 1992;Crowley et al, 1993;Duffy, 1993). We determined several components of the PA system in carcinomatous tissue and adjacent normal mucosa in a subgroup of 136 Dukes' stage B or C colorectal carcinoma patients, and evaluated their prognostic value for overall survival in comparison with several major clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of plasminogen activators is regulated by the plasminogen activator inhibitors PAI-I and PAI-2. In vitro experiments with human carcinoma cell lines have shown that invasion and metastasis are correlated with enhanced expression of u-PA, and that these processes could be inhibited by antibodies against u-PA and by blocking of the u-PA receptor (Ossowski et al, 1991;Quax et al 1991;Crowley, 1993).…”
mentioning
confidence: 99%